P056 Influence of country of birth on risk of STI diagnosis among black Caribbeans in England in 2014. (30th June 2016) - Harb, Ana; Mohammed, Hamish; Furegato, Martina; Hughes, Gwenda
Abstract : Background/introduction: In England, people of Black Caribbean (BC) ethnicity are disproportionately affected by sexually transmitted infections (STIs), but it is unclear whether this is associated with their country of birth. Aim(s)/objectives: To examine differences in STI diagnoses among UK- and Caribbean-born BC people. Methods: Data on STI diagnoses in BC people attending genitourinary medicine (GUM) clinics and living in England were obtained from the GUM Clinic Activity Dataset (GUMCADv2). Associations between being UK- or Caribbean-born and diagnosis with an STI were derived using univariate and multivariable multilevel logistic regression models adjusted for age, gender/sexual-orientation, residence, and HIV status. Results: BC people made 231, 719 attendances in 2014; 81.9% were UK-born. The median age (years) was 25 for UK-born and 34 for Caribbean-born people (p ≤ 0.001). Chlamydia, non-specific genital infection and gonorrhoea were the most commonly diagnosed STIs among UK- (37.4%, 19.5% and 13.7%) and Caribbean-born attendees (32.1%, 25.2% and 13.1%). From the multilevel analysis, UK-born attendees were less likely to be diagnosed with chlamydia (aOR 0.87 [95%C.I. 0.81–0.94]) and trichomoniasis (0.83 [0.71–0.97]), and more likely to be diagnosed with genital warts (1.24 [1.07–1.45]) than Caribbean-born attendees. The adjusted odds of a gonorrhoea diagnosis did not vary by country of birth. Discussion/conclusion: STI rates among black Caribbeans attending GUM clinics in England are high and might be influenced by STI epidemiology in their country of birth. Studies on the effectiveness of interventions aimed at reducing the burden of STIs in all black Caribbeans are urgently needed.